2022
DOI: 10.1007/s10554-022-02737-2
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular strain patterns in multivalvular heart disease: a cross-sectional study

Abstract: Multivalvular heart disease (MVD) is an aggregate of regurgitant and/or stenotic lesions of at least two cardiac valves. Ventricular tissue deformation imaging is a powerful predictor of subclinical myocardial dysfunction in patients with MVD.The aim of this study was to examine the left and right ventricular strain patterns in MVD as well as observe any association between right–sided valvular involvement (tricuspid or pulmonary valve lesion) with that of aortic and/or mitral valve lesion. Patients with at le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Once the region of interest is chosen, the software automatically presents the strain and strain rate curve forms for various areas, along with a Bull's eye representation of the 17 segments. Strain rates at peak systole, early diastole and late diastole were obtained 4 .GLS was calculated automatically as the average of global peak systolic strain from each of three views. Out of 258 patients, 111 had regular follow up and all the parameters were taken again and adverse outcomes noted.…”
Section: Methodsmentioning
confidence: 99%
“…Once the region of interest is chosen, the software automatically presents the strain and strain rate curve forms for various areas, along with a Bull's eye representation of the 17 segments. Strain rates at peak systole, early diastole and late diastole were obtained 4 .GLS was calculated automatically as the average of global peak systolic strain from each of three views. Out of 258 patients, 111 had regular follow up and all the parameters were taken again and adverse outcomes noted.…”
Section: Methodsmentioning
confidence: 99%
“…The study found that LV-GLS in these patients were preserved whereas RV-GLS was mildly reduced. The author concluded that higher level of pulmonary pressure and RV pressure overload lead to these ndings 43 . Similar results were found in the present study.…”
Section: Ventricular Functionmentioning
confidence: 99%
“…To date, data on the diagnostic and prognostic utility of strain analysis in MVD are lacking. A study on 72 patients showed that LV strain parameters were not altered, but RV strain parameters were mildly reduced, suggesting an overload of the RV due to the presence of combined left-sided valvulopathies [ 56 ]. Further studies are needed to investigate the role of deformation index analysis in patients with MVD.…”
Section: Advanced Echocardiography and Multimodality Imagingmentioning
confidence: 99%